1998
DOI: 10.1074/jbc.273.1.528
|View full text |Cite
|
Sign up to set email alerts
|

Integrin-linked Protein Kinase Regulates Fibronectin Matrix Assembly, E-cadherin Expression, and Tumorigenicity

Abstract: Cell-extracellular matrix and cell-cell interactions play critical roles during many physiological and pathological processes including morphogenesis and tumorigenesis. Many of the cellextracellular matrix and cell-cell interactions are mediated by cell adhesion molecules that are members of the integrin and cadherin families. Integrins are ␣␤ heterodimeric transmembrane glycoproteins that interact with extracellular (or other cell surface) molecules and cytoplasmic molecules, including cytoskeletal and cataly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
212
3
1

Year Published

1998
1998
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 269 publications
(235 citation statements)
references
References 72 publications
19
212
3
1
Order By: Relevance
“…Cell survival and cell growth regulated by growth factor signalling (Moustakas et al, 2002;Neve et al, 2002) have been shown by Wu et al (1998) to be also substantially affected by ILK signalling upon ligand binding to b1-integrin receptors. The ILK signalling cascade seems to be involved in tumour growth, tumorigenesis and in the development of a metastatic phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Cell survival and cell growth regulated by growth factor signalling (Moustakas et al, 2002;Neve et al, 2002) have been shown by Wu et al (1998) to be also substantially affected by ILK signalling upon ligand binding to b1-integrin receptors. The ILK signalling cascade seems to be involved in tumour growth, tumorigenesis and in the development of a metastatic phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…This relation may be a direct effect from tumor to normal adjacent cells, a secondary effect because of specific characteristics conferred on the tumor by SNAI1 expression or related to other unknown alterations. For example, changes in secreted matrix proteins by tumor cells could modulate the expression of CDH1 in adjacent cells through the activation of the integrin-linked kinase (Lochter et al, 1997;Wu et al, 1998;Menke et al, 2001). This effect might be mediated by SNAI1 activation in adjacent cells, as SNAI1 transcription is stimulated by integrinlinked kinase activation in colon cells (Tan et al, 2001).…”
Section: Adh-gfp Adh-sn Row Column Cytokine Cytokinefull Name Median mentioning
confidence: 99%
“…Overexpression of ILK in normal epithelial cells (Scp2 mouse mammary epithelial cells and IEC-18 rat intestinal epithelial cells) results in anchorageindependent growth, 36 cell-cycle progression 37 and tumorigenicity in nude mice. 38 The apparent contradiction between these 2 models may be due to the cellular context in which ILK was expressed. Normal epithelial cells express optimal levels of ILK, whereas the MDA-MB-435 cells have sub-threshold ILK expression.…”
Section: Growth-inhibitory Functions Of Ilkmentioning
confidence: 99%
“…This in turn induces anchorage-independent growth, 36 cell-cycle progression 37 and tumorigenicity in nude mice. 38 Clearly, the functions of ILK are more complex than previously envisioned, and the divergent and often paradoxical effects mediated by ILK may depend on the particular cell type, cell environment and the cell-specific integrins that are activated.…”
Section: Growth-inhibitory Functions Of Ilkmentioning
confidence: 99%